Analisis Ekonomi Broiler yang Diberi Ekstrak Kulit Manggis (Garcinia mangostana L) dalam Ransum - R Pratiwi; R Noviadi; Z Zairiful (PETERPAN (Jurnal Peternakan Terapan), 2022)
Study aims to analyze the production costs and revenues using mangosteen peel extract in broiler. The research was carried out for 3 months at  farm in Department of Animal Husbandry, Lampung State Polytechnic. This study used 5 treatments, the treatments were P0 (100% control diet), P1 (Control Diet+ 0.5% mangosteen peel extract 0.5%, P2 (Control Diet+1% mangosteen peel extract 1%), P3 (Control Diet + 1.5% mangosteen peel extract), and P4 (Control Diet + 2% mangosteen peel extract). The data obtained were calculated using Microsoft Excel and analyzed descriptively. The results of the study showed that the use of mangosteen peel extract in diets rations up to a level of 2% was able to reduce production costs. The best results were found in the use of  1% (P2) with a BEP(Break Event Point) value of Rp. 21,135.86, IOFC(Income Over Feed Cost) Rp. 537,613.92, R/C (Revenue cost ratio) 1.40 and  B/C (Benefit cost ratio)  0.40